Market participation, household food security, and income: The case of cowpea producers in northern Nigeria. (2nd June 2020) - Manda, Julius; Alene, Arega D.; Tufa, Adane Hirpa; Feleke, Shiferaw; Abdoulaye, Tahirou; Omoigui, Lucky O.; Manyong, Victor
Abstract: This article evaluates the impact of cowpea market participation on household food security and income in northern Nigeria. Using household survey data from a representative sample of over 1, 500 farm households and applying a combination of instrumental variable techniques and dose–response functions, we found that cowpea market participation had a statistically significant positive impact on household food security and income. Cowpea market participation increased food expenditure by 1.6% and household income by 0.7% with a 10 unit increase in the quantity of cowpea sold. These results underscore the importance of cowpea market participation for household food security and income improvement. We also found that selling cowpea to rural and urban traders significantly increased household income, food expenditure, and food security. Results show that selling cowpea to rural and urban traders increased household income by 17% and 13%, respectively. The results point to the need for an enabling policy environment and public infrastructure to enhance market participation of farmers and traders. Public infrastructure investments in the form of feeder road construction and maintenance in the distant villages are encouraged, which in the long run can translate into improved cowpea productivity and welfare of smallholder farmers. Abstract : This paper evaluates the impact of cowpea market participation on household food security and household income in northern Nigeria. We find that cowpea market participation has a positive and significant effect on household food security and income.